DEVELOPMENT OF DISTANCE EDUCATION SYSTEM IN ICIT TANE - Bilousov, Igor; Novosad, Oleksander; Adamiv, Oleh (International Journal of Computing, 2014)
In the presented material particularises of functioning of the distance education centre as well as consultant centres are considered. Also we consider development of such education system in Institute of Computer Information Technologies (ICIT) of Ternopil Academy of National Economy (TANE).